The Role of Bhabinkamtibmas in Preventing Drug Abuse in the Legal Territory of Muara Enim Police - Herwin Jonathan Nababan (Indonesian Journal of Police Studies, 2021)
Drug abuse in the Muara Enim Regency area is based on data on revealing drug cases owned by the Narcotics Unit of the Muara Enim Police, which increased in 2019. The increase in data on disclosing drug abuse cases can be said to be for those carrying out the pre-emptive and preventive functions of a failure. Bhabinkamtibmas is the spearhead of the Binmas Unit because it interacts directly with the community in the kelurahan/village. Therefore, the author takes the title "The Role of Bhabinkamtibmas in Preventing Drug Abuse in the Legal Territory of the Muara Enim Police Station." The theory used is management theory and role theory to analyze overcoming drug abuse, while the concepts used by the author are the concept of prevention, the concept of Bhabinkamtibmas and the concept of Narcotics to better understand in depth the meaning of Bhabinkamtibmas and drugs. The purpose of the study was to describe and analyze the role of Bhabinkamtibmas and the influencing factors in overcoming drug abuse in Muara Enim Regency. This research was conducted with a qualitative approach with data collection techniques using interviews, observations, and document studies to obtain a comparison between theory and practice. The results showed that the constraints found were the quantity and quality of personnel, inadequate budget, inadequate infrastructure, and inappropriate implementation methods. While the role of Bhabinkamtibmas is to provide guidance and counseling to the community in its fostered villages. Suggestions from the author for the Muara Enim Police Station (1) add the quantity and quality of personnel (2) provide vocational or training (3) carry out planning regarding the budget and infrastructure (4) make method guidelines as a reference for implementation.